DOMINASI PERAN PURI DALAM KONTESTASI POLITIK DI BALI (STUDI KASUS : PURI AGUNG DENPASAR) - Mas Mahadewi, Ida Ayu (Jurnal Nawala Politika, 2017)
This research is motivated by Puri Agung Denpasar which is a traditional institution which is currently experiencing a cultural upheaval due to the occurrence of modernity in the city of Denpasar unnoticed the function of the castle as a traditional power increasingly marginalized. But Puri Agung Denpasar is also attached to the stigma as a political castle seen from the dominating figures of the puri family who occupy important positions in government. Thus the question arises how the form of domination by the castle in political contestation in Bali. The theory used in this issue is Client Patron Theory, and Social Network Theory. The research method used is qualitative research with three techniques of data collection, namely observation, interviews, and document studies. Data were analyzed by qualitative analysis technique. The result of the research shows that underlying Puri Agung Denpasar can dominate in political contestation until now because of the solid internal relationships of Puri Agung Denpasar family, followed by the role of the puri family in establishing good relations with the community, then the puri's effort to make the establishment of interpuri and expansion of social networks. Followed by strengthening the castle as a cultural heritage. The results of this study indicate that Puri Agung Denpasar tends to successfully expand its dominance including in the field of practical politics. Keywords           : Puri Agung Denpasar, Domination, Political Contestation